Development of the Chilean front-of-package food warning label - Marcela Reyes; María Luisa Garmendia; Sonia Olivares; Claudio Aqueveque; Isabel Zacarías; Camila Corvalán (BMC, 2019)
Abstract Background Front-of package (FoP) nutrition labels are an option to guide consumer's decision at the point of food purchase. Chile was the first country worldwide to implement a FoP warning label and thereafter several countries have followed this model. The objective of this study is to describe the process of development of the Chilean FoP warning label. Methods A stepwise study was conducted including literature review, qualitative phase (lay audience & expert group meetings) and quantitative phase in women/adolescents from low-middle-socioeconomic status neighborhoods, Santiago, Chile (2 sub-studies, using point-of-sale questionnaires). Outcomes were prototype visualization, ease of understanding, and ability to modify purchase behavior. Results The literature review and qualitative phase provided information on general text (e.g. short wording) and design characteristics (e.g. use of a logo, use of red or black colors); based on these characteristics 15 prototypes were created and quantitatively tested. In the first survey, a black-&-white stop sign and a black-&-white hand were preselected; in the second survey, the stop sign stating 'Excess of <nutrient>' had significantly better performance than the hand in terms of visualization, intention to purchase, and ability to modify intended purchase. Due to legal reasons the "excess of" was replaced by "high-in" in the final implementation of the law. Conclusions A simple black-&-white stop sign warning label was the best option to flag pre-packaged foods with an excess of energy or nutrients of concern for non-communicable diseases; this FoP warning label was implemented in Chile in June 2016 as part of the Chilean Food Labeling and Marketing Law.